2015
DOI: 10.18433/j3tg88
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Transport Inhibition by Dipyridamole Prevents Angiogenesis Impairment by Homocysteine and Adenosine

Abstract: -Purpose. Adenosine plays an important role in the pathogenesis of homocysteine-associated vascular complications. Methods: This study examined the effects of dipyridamole, an inhibitor for nucleoside transport, on impaired angiogenic processes caused by homocysteine and adenosine in human cardiovascular endothelial cell line (EAhy926). Results: The results showed that dipyridamole restored the extracellular adenosine and intracellular S-adenosylhomocysteine concentrations disrupted by the combination of homoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Consistent with the previous findings [ 27 , 33 , 34 ], we have successfully established the Hcy-impaired cell proliferation, migration and tube formation model on EAhy 926 cells. Our results showed that Hcy and Ado impaired angiogenesis in these three assays in a concentration and time-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the previous findings [ 27 , 33 , 34 ], we have successfully established the Hcy-impaired cell proliferation, migration and tube formation model on EAhy 926 cells. Our results showed that Hcy and Ado impaired angiogenesis in these three assays in a concentration and time-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, there is increasing evidence to suggest the importance of Hcy as a new and important risk factor/independent predictor for vascular diseases such as ischaemic heart diseases and stroke. An accumulation of Hcy, often referred to as hyperhomocysteinaemia, has been shown to concentration-dependently impair endothelial cell proliferation and survival together with Ado and ultimately lead to vascular dysfunction [ 25 , 26 , 27 ]. It is suggested that increased extracellular level of hyperhomocysteinaemia in response to cell injury and stress (i.e., ischemia) with Ado [ 28 , 29 ] produces elevated extracellular S-adenosylhomocysteine which in turn, reduces the intracellular mRNA and protein expressions of fibroblast growth factor (FGF2) via G-protein receptor thus, leading to endothelial anti-proliferation (Hcy = 50–100 µM) and anti-survival activity (Hcy > 100 µM) [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a multifunctional molecule dynamically involved in different tissues and responses in the body. It has been associated largely with the pathogenesis of vascular problems (Kam et al, 2015). One of the present study conduction was to evaluate ADA and GSH levels in adenosine treated rabbits, the results showed highly signi icant mean levels of ADA in adenosine group when compared to controls, this can be explained by fact that ADA is one of the enzymes that are responsible for adenosine activity.…”
Section: Resultsmentioning
confidence: 54%
“…This angiogenic ability of adenosine could explain the results of the present study manifested by increased vascularity, congestion of blood vessels and hemorrhage. Although the mechanism by which adenosine induces angiogenesis is poorly understood, numer-ous studies have shown that the exogenous adenosine as well as endogenous adenosine can modulate VEGF expression and other angiogenic factors (Kam et al, 2015;Maugeri et al, 2019). in a different cell types.…”
Section: Resultsmentioning
confidence: 99%